Provisional checklist for the lichens of Chiapas - Sipman, Harrie J. M.; Wolf, Jan H. D. (Instituto de Ecología, A.C., 1998)
A list is presented of 359 lichen taxa known so far from Chiapas (Mexico). It is based on literature records and recent collections made by Breedlove and by Wolf and collaborators. The actual lichen flora of Chiapas is estimated to be certainly much larger.